HEALTH BEHAVIORS AND RACIAL DISPARITY IN BLOOD PRESSURE CONTROL IN THE NATIONAL HEALTH AND NUTRITION EXAMINATION SURVEY - Redmond, Nicole (2011)
Minorities have a higher prevalence of hypertension, a major risk factor for cardiovascular disease, which contributes to racial/ethnic disparities in morbidity and mortality in the US. Many modifiable health behaviors have been associated with improved blood pressure control, but it is unclear how racial/ethnic differences in these behaviors are related to the observed disparities in blood pressure control. Cross-sectional analyses were conducted among 21,489 US adults aged >20 years participating in the National Health and Nutrition Examination Survey from 2001–2006. Secondary analyses were conducted among those with a self-reported diagnosis of hypertension. Blood pressure control was defined as systolic values <140 mmHg and diastolic values <90 mmHg (or <130 mmHg and <80 mmHg among diabetics, respectively). In primary analyses, Non-Hispanic Blacks had 90% higher odds of poorly controlled blood pressure compared to non-Hispanic Whites after adjustment for sociodemographic and clinical characteristics (p <0.001). In secondary analyses among hypertensive subjects, non-Hispanic Blacks and Mexican-Americans had 40% higher odds of uncontrolled blood pressure compared to non-Hispanic Whites after adjustment for sociodemographic and clinical characteristics (p <0.001). For both analyses, the racial/ethnic differences in blood pressure control persisted even after further adjustment for modifiable health behaviors, which included medication adherence in secondary analyses (p <0.001 for both analyses). Although population-level adoption of healthy behaviors may contribute to reduction of the societal burden of cardiovascular disease in general, these findings suggest that racial/ethnic differences in some health behaviors do not explain the disparities in hypertension prevalence and control.